The Effect of Wear Particles from Joint Prostheses Materials to Bone Cells Number - Suhartini, Suhartini (The Indonesian Journal of Dental Research)
Background: The wear particles of joint prostheses can induce releasing of inflammatory mediators. Releasing of inflammatory mediators from activated inflammatory cells can lead bone cells respons. Methods: Wear particles generated by wear testing of both materials Ultra High Molecular Weight Polyethylene (UHMWPE) GUR 1120 and Stainless Steel 316 L with ion implantation by using pin on plate unidirectional motion machine and phosphate buffer saline (PBS) as lubricant. The velocity of running wear test is 116.5 mm/s and the sliding distance was 30 km. Furthermore, wear particles was inserted into knee joint synovium capsule of Rattus norvegicus sp. The animals were sacrificed to know the number bone cells on seventh day. Results: Statistical analysis by Kruskal Wallis showed that there was no significant differences in the number of osteoblast cells (p=0.094) and there were no significant differences in the number of osteoclast cells (p=0.143). Conclusion: There was no effect of wear particles from joint prosthesesto bone cells number